2005
DOI: 10.1016/j.atmosenv.2004.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and seasonal cycles of ozone precursors observed from continuous measurement at an urban site in Taiwan

Abstract: Hourly measurement of 56 ozone precursors was conducted by a monitoring station located in a metropolitan area in central Taiwan. After nearly a year of continuous operation at this urban site, both diurnal and seasonal cycles of nonmethane hydrocarbons (NMHCs) were clearly observed, which were caused by the interplay between source, chemical loss, and meteorology. Selected species representing three different types of major sources, namely, the household fuel leakage, vehicular exhaust and gasoline evaporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…The morning peak (0.99 ppm at 08.00 h) was lower in magnitude than that of the late evening peak (2.07 ppm at 21.00 h). This two-peak pattern had also been observed in many other sites, such as Changchun, China (Liu et al, 2000); Taichung, Taiwan (Yang et al, 2005); and Bilbao, Spain (Durana et al, 2006). The pattern suggested that the dominant effect in the early morning and late evening was of traffic density, that resulted in the increase of exhaust from vehicles.…”
Section: Concentrationssupporting
confidence: 64%
“…The morning peak (0.99 ppm at 08.00 h) was lower in magnitude than that of the late evening peak (2.07 ppm at 21.00 h). This two-peak pattern had also been observed in many other sites, such as Changchun, China (Liu et al, 2000); Taichung, Taiwan (Yang et al, 2005); and Bilbao, Spain (Durana et al, 2006). The pattern suggested that the dominant effect in the early morning and late evening was of traffic density, that resulted in the increase of exhaust from vehicles.…”
Section: Concentrationssupporting
confidence: 64%
“…Thus, speciated non-methane hydrocarbons (NMHCs) were continuously monitored by photochemical assessment monitoring stations (PAMS) on the island operated by Taiwan Environmental Protection Administration (EPA) since 2002 to provide hourly mixing ratios of 54 C 2 to C 12 species by automated GC with flame ionization detection (FID) (Yang et al, 2005;Chang et al, 2010). The PAMS NMHCs were calibrated every five days by analyzing a gas mixture at sub-ppb levels (Scott Specialty Gas, U.S).…”
Section: Methodsmentioning
confidence: 99%
“…VOCs of anthropogenic origin, including aromatics and C 4 -C 6 alkanes, have higher mixing ratios in winter. This difference can be explained by three factors (Boudries et al, 1994;Cheng et al, 1997;Na and Kim, 2001;Swanson et al, 2003;Yang et al, 2005;Shirai et al, 2007): (i) a stronger temperature inversion in winter than in summer, leading to a mean daytime boundary layer 3 times shallower in winter than in summer at SIRTA (440 ± 220 m and 1340 ± 610 m, respectively, between 9 a.m. and 6 p.m.) (Filella and Peñuelas, 2006); (ii) lower OH radical concentrations in winter and thus less depletion by photochemistry (Michoud et al, 2012(Michoud et al, , 2014; and finally (iii) sources of different nature, composition and/or strengths. Different primary anthropogenic sources are known to be subject to the seasonal variations detailed in the last assumption, among these is the fuel evaporation.…”
Section: Seasonal Variations Of Vocsmentioning
confidence: 99%